Nghiên cứu sự hấp phụ As(V) trong dung dịch nước trên vật liệu Fe-bentonit - Mỹ Linh, Nguyễn Lê; Thanh Lai, Nguyễn Thị; Quang, Dương Tuấn; Khiếu, Đinh Quang; Phú, Nguyễn Hữu (Vietnam Journal of Chemistry, 2015)
Adsorption of arsenate [As(V)] from aqueous solution onto Fe-bentonite was studied. Batch adsorption studies were carried out on the adsorption of As(V) as a function of contact time, pH, and initial metal concentration. X-ray diffraction (XRD) analysis, thermal analysis (TG - DTA), and surface area analysis indicated that poly-hydroxy-Fe or polyoxo-Fe cations were intercalated into layers of montmorillonite, resulting in an increase of d001 value and of the specific surface area compared with those of raw bentonite. The results indicated that the maximum adsorption of Fe-bentonite was obtained at the pH 3.0 for As(V). The adsorption data was analyzed by both Freundlich and Langmuir isotherm models and the data was well ﬁt by the Langmuir isotherm model. Kinetic data correlated well with the pseudo-second-order kinetic model. Thermodynamic studies showed that the adsorption process was endothermic and spontaneous in nature.